Development of Corn Ice Drink Products as Micro Business Innovation to Increase Product Sales Value - Yasni La Jalia; Sakina Sudin; Evitawati Indradewa; Nurul Sari Umaternate; Sarni Abd. Kadir (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the community’s economy, particularly in the culinary and beverage sector. One traditional beverage that is widely favored by the public is sweet corn ice drink. However, sweet corn ice products marketed by MSMEs generally still lack product and packaging innovation, resulting in low selling value and limited competitiveness. This Program Kreativitas Mahasiswa (PKM) activity aims to develop sweet corn ice beverages through product and packaging innovation in order to increase the product’s selling value. The implementation method used a participatory approach involving students and MSME partners through several stages, including observation, product development design, innovation implementation, and evaluation. The innovations applied included the design of a visual identity in the form of a product logo, the use of labeled cup packaging, and improvements in product presentation. The results indicate that product and packaging innovation can enhance product attractiveness, strengthen business identity, and potentially increase sales volume and MSME income. Therefore, the development of sweet corn ice beverages through simple but targeted innovation can serve as an effective solution to increase product value and support the sustainability of micro-enterprises.